Testosterone-treated cows to aid in heat detection - G.N. Laaser; G.H. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1977)
Eight cull Hereford cows were given 200-mg. injections of testosterone proprionate repository (Haver-Lockhart, Shawnee, KS) every other day for 20 days (10 injections). Four cows were given weekly booster injections with the same testosterone proprionate; the other four were injected every three weeks with testosterone enanthate (sigma Chemical Co., St. Lois, MO.). Each cow was equipped with a chin-ball marker and each was used to detect heat in other cows. The detection period lasted approximately 45 days. Testosterone-treated cows served satisfactorily as heat detectors; those given boosters of testosterone proprionate marked more cows in heat than those given testosterone enanthate.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Testosterone; Heat detection